SISTEM INFORMASI IT-HELPDESK PADA UNIVERSITAS AMIKOM YOGYAKARTA BERBASIS WEB - Ali Mustopa (JURNAL INFORMATIKA DAN KOMPUTER, 2017)
IT Helpdesk is a service unit that is responsible to help in overcoming the problems related to the usage of ICT facilities at Universitas AMIKOM Yogyakarta. IT Helpdesk provides some form of services that can be utilized by academic community at Universitas AMIKOM Yogyakarta in usage of ICT services. This unit services include installation, troubleshooting software, service and computer maintenance. This research discusses about how information system development for user, consumer and manajamen IT Helpdesk. IT Helpdesk of Universitas AMIKOM Yogyakarta currently has an information system that includes the management of user registration and financial data. However, there is no information systems that provides detailed information from the consumer, which can be utilized by consumers IT Helpdesk itself in tracking the services status. Additionally, the current system has not been able to support management requirements in monitoring and evaluating the performance of technicians. The results of the research is a system that can provide information with a fast and accurate to the consumer and management of IT Helpdesk.